Satisfaction and Service Quality of Using High-Speed 4G Wireless Broadband in University Campus - Daud, Norzaidi Mohd; Kamal, Mohd Adi Mohd; Zaharudin, Mohd Zuhair; Jumhar, Yang Haniza; Mohamed, Intan S. (Asian Business Review, 2018)
This paper aims to examine customers’ satisfaction with the product service quality rendered by high-speed 4G wireless broadband (YES!) and YES! Campus Store. 161 of 300 students were engaged from numerous faculties at Universiti Teknologi MARA, Shah Alam, Selangor, Malaysia. Based on a survey, this study suggested that tangibility, reliability, responsiveness, assurance, and empathy produce negative results. It shows that the service rendered by YES! does not meet the expectation of customers’ satisfaction. This paper draws attention to the importance of having high-speed 4G wireless broadband in the campus as its impact on customers’ satisfaction as well as service quality at YES! campus store.
Keywords: Customers’ satisfaction; service quality; high speed internet; 4G wireless broadband; UiTM campus